YEVHEN OLESNYTSKYI – THE GUIDE OF THE UKRAINIAN PEASANTRY: PART 2 - MARKIV, Inna; HOMOTUK, Oksana (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2025)
The peculiarities of the functioning of the «Silskyi Hospodar» society from its foundation to reorganization have been tracked. The circumstances of the leadership of the society by Y. Olesnytskyi in 1909 and its reconstruction on new foundations as a representative institution of the Ukrainian peasantry are analyzed. The role of the first agricultural exhibition in Eastern Galicia in the reformation of «Silskyi Hospodar» is shown. The new tasks of the institution's activities and prospects for the development of the institution, proposed by its head Y. Olesnytskyi, were studied. Emphasis is placed on the facts of the «Silskyi Hospodar» receiving state subsidies as financial compensation for Galician-Ukrainian peasants for unfair international trade agreements. The main aspects of the activity of the association headed by Y. Olesnytskyi in the direction of reorganization of animal husbandry, agriculture, rivers regulation, etc. have been determined. The work of the «Silskyi Hospodar» in providing Galician-Ukrainian peasants with means of production, fodder, seeds, as well as measures for the sale of agricultural products, was studied. The effectiveness of the institution is shown through its implementation of such management functions as control and accounting of the activities of branches, careful management of records, improvement of the charter, provision of a clear organizational and administrative structure, cooperation with other state economic organizations, etc. The plans of the chairman of the «Silskyi Hospodar» association Y. Olesnytskyi for the post-war economic reconstruction of the region have been recorded.